ATP Induces Disruption of Tight Junction Proteins via IL-1 Beta-Dependent MMP-9 Activation of Human Blood-Brain Barrier In Vitro - Fuxing Yang; Kai Zhao; Xiufeng Zhang; Jun Zhang; Bainan Xu (Neural Plasticity)
Disruption of blood-brain barrier (BBB) follows brain trauma or central nervous system (CNS) stress. However, the mechanisms leading to this process or the underlying neural plasticity are not clearly known. We hypothesized that ATP/P2X7R signaling regulates the integrity of BBB. Activation of P2X7 receptor (P2X7R) by ATP induces the release of interleukin-1β (IL-1β), which in turn enhances the activity of matrix metalloproteinase-9 (MMP-9). Degradation of tight junction proteins (TJPs) such as ZO-1 and occludin occurs, which finally contributes to disruption of BBB. A contact coculture system using human astrocytes and hCMEC/D3, an immortalized human brain endothelial cell line, was used to mimic BBB in vitro. Permeability was used to evaluate changes in the integrity of TJPs. ELISA, Western blot, and immunofluorescent staining procedures were used. Our data demonstrated that exposure to the photoreactive ATP analog, 3′-O-(4-benzoyl)benzoyl adenosine 5′-triphosphate (BzATP), induced a significant decrease in ZO-1 and occludin expression. Meanwhile, the decrease of ZO-1 and occludin was significantly attenuated by P2X7R inhibitors, as well as IL-1R and MMP antagonists. Further, the induction of IL-1β and MMP-9 was closely linked to ATP/P2X7R-associated BBB leakage. In conclusion, our study explored the mechanism of ATP/P2X7R signaling in the disruption of BBB following brain trauma/stress injury, especially focusing on the relationship with IL-1β and MMP-9.